2013
DOI: 10.3389/fimmu.2013.00464
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Network Model of MHC Class II-Restricted Antigen Processing

Abstract: The standard model of Major Histocompatibility Complex class II (MHCII)-restricted antigen processing depicts a straightforward, linear pathway: internalized antigens are converted into peptides that load in a chaperone dependent manner onto nascent MHCII in the late endosome, the complexes subsequently trafficking to the cell surface for recognition by CD4+ T cells (TCD4+). Several variations on this theme, both moderate and radical, have come to light but these alternatives have remained peripheral, the conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 143 publications
(128 reference statements)
0
11
1
Order By: Relevance
“…In a more recent study, Miller et al (15) showed that initiation of CD4 + T cell responses to influenza virus is driven predominantly by endogenous Ags expressed within the infected APC. Taken together, these findings challenge the notion that a single epitope's fate is sealed by its origin, and, instead, they indicate that commitment to its processing or presentation pathways depends on the Ag source, localization, and type of APC (16,17).…”
Section: A Ccumulating Evidence Suggests That Hiv-specific (Hs) Cd4contrasting
confidence: 47%
“…In a more recent study, Miller et al (15) showed that initiation of CD4 + T cell responses to influenza virus is driven predominantly by endogenous Ags expressed within the infected APC. Taken together, these findings challenge the notion that a single epitope's fate is sealed by its origin, and, instead, they indicate that commitment to its processing or presentation pathways depends on the Ag source, localization, and type of APC (16,17).…”
Section: A Ccumulating Evidence Suggests That Hiv-specific (Hs) Cd4contrasting
confidence: 47%
“…For many years alternatives to the classical MHC-II processing pathway have been recognized. These include loading of “recycling” MHC-II in an early endosomal compartment [5658] and endogenous processing, in which peptide is derived from antigen synthesized within the APC, often via processing mechanisms that extend beyond the endocytic compartment [59]. Until recently, these alternatives have been considered marginal.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent work from our laboratory suggests that peptides derived from endogenous processing drive the vast majority of the response to infectious influenza [60*]. Furthermore, we have observed endogenous processing to be comprised of an array of pathways, sufficiently complex for us to propose the term “processing network” [59, 60*]. Recently, a similar level of complexity has been reported for the extra-endosomal generation of the human MHC-II-restricted self-peptidome [61*].…”
Section: Discussionmentioning
confidence: 99%
“…Though elucidation of the exact mechanisms that generate self-pMHC able to mediate thymic selection is ongoing, it is clear they are complicated in nature and challenge our current understanding of antigen processing. Involvement of antigen processing machinery outside of the “classical” pathways may prove to play a vital role in establishing the selecting ligandome that leads to functional and self-tolerant CD4 and CD8 T cell repertoires (Miller et al, 2013). Unequivocal determination of which model, or more likely, combination of models, most accurately reflects in vivo thymocyte selection depends intimately upon gaining an understanding of the landscape of selecting self-pMHC complex expression.…”
Section: Introductionmentioning
confidence: 99%